"Competence approach of english teaching language in Ngabe Bugle ethnicity to students of 6th grade in Quebrada de Hacha Elementary Schoo, San Lorenzo District, 2013" - Gutiérrez, Dina (UDELAS, 2013)
This approach allows students to develop all their skills in an acative way, in the city and in the indigenous area where was developed this reseach project.